A history of science and its relations with philosophy & religion - Dampier, William Cecil (University Press, 1948)
This famous book, first published in 1929 was considerably revised and enlarged in its fourth edition, which is being reprinted now. This edition had the addition of a postscript by Professor I. Bernard Cohen containing a list of reading, with comments on them to guide the readers.